Detection of Cracks in Concrete Structure Using Microwave Imaging Technique - Jiya, E. A.; Anwar, N. S. N.; Abdullah, M. Z. (Hindawi Publishing Corporation, 2016)
Cracks in concrete or cement based materials present a great threat to any civil structures; they are very dangerous and have caused a lot of destruction and damage. Even small cracks that look insignificant can growandmay eventually lead to severe structural failure. Besides manual inspection that is ineffective and time-consuming, several nondestructive evaluation techniques have been used for crack detection such as ultrasonic technique, vibration technique, and strain-based technique; however, some of the sensors used are either too large in size or limited in resolution. A high resolution microwave imaging technique with ultrawideband signal for crack detection in concrete structures is proposed. A combination of the delay-and-sum beamformer with full-view mounted antennas constitutes the image reconstruction algorithm. Various anomaly scenarios in cement bricks were simulated using FDTD, constructed, andmeasured in the lab. The reconstructed images showed a high similarity between the simulation and the experiment with a resolution of